Strengthening the Role of Village-Owned Enterprises Through Coaching in Rato Village, Lambu District, Bima Regency - Asmiatiningsih, Sri; Iptidaiyah, Muhamad; Tasrif, Tasrif; Hendra, Hendra; Junaidin, Junaidin; Ardiansyah, Nike; Usman, Ahmad; Nurlaila, Nurlaila (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Village-Owned Enterprises (BUMDes) play a crucial role in improving the welfare of rural communities through local economic empowerment. In Rato Village, Lambu District, Bima Regency, BUMDes functions as the driving force for village economic development. However, in its implementation, BUMDes in this village still faces various challenges related to management, funding, and human resource development. The aim of this study is to identify the efforts made to strengthen the role of BUMDes in Rato Village and to assess its impact on the local economy. A qualitative method with a case study approach was used. Data were collected through interviews with village officials, BUMDes managers, and local community members. The results show that the capacity building efforts, including business management training, financial assistance, and local product development, have had a positive impact on the performance of BUMDes. However, continued efforts are needed to improve the capacity of managers and expand the scope of BUMDes activities in the future.